DEVELOPMENT OF AN INTERACTIVE AI-BASED TOOL FOR AUTOMATIC PRONUNCIATION ASSESSMENT IN FOREIGN LANGUAGE LEARNING (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2026)
This paper presents the development of an AI-based interactive web platform designed for automatic pronunciation assessment and improvement in foreign language learning. The system analyzes learner speech using speech recognition and deep learning models, detects pronunciation errors, and provides adaptive feedback in Uzbek. The proposed framework integrates pronunciation accuracy, user engagement, adaptive learning mechanisms, and real-time feedback into a unified evaluation model. Experimental results demonstrate that regular use of the platform significantly improves pronunciation accuracy, intelligibility, and learner confidence. The findings confirm the effectiveness of AI-driven adaptive learning systems in enhancing foreign language pronunciation training.
Keywords: artificial intelligence; pronunciation assessment; speech recognition; adaptive learning; interactive web platform; CAPT systems